Pengembangan Media Pembelajaran Bangun Ruang Berbasis Augmented Reality untuk Kelas V Sekolah Dasar - Maulidia, Maulidia; Sutrisno AB, Joko; Lestari, Yulita Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2024)
This research aims to develop Augmented Reality-based learning media on spatial material that is suitable for use as a mathematics learning media for fifth grade elementary school students. This research uses the R&D (research and development) method with the ADDIE development model. The feasibility of the learning media developed is reviewed from validity by material, media and language experts. In addition, the responses of educators and students to the use of the learning media developed were analyzed. The research was carried out at SD Negeri 2 Susunan Baru in the 2023/2024 academic year. Based on the validation results of material experts, media experts and language experts, it is known that the Augmented Reality-based spatial learning media developed is very feasible. After implementation and evaluation activities, it was discovered that the response of educators and students to the use of Augmented Reality-based learning media was very interesting. Thus it can be concluded that the learning media developed based on Augmented Reality is very feasible and very interesting to use as a learning media for mathematics learning in spatial building material for class V elementary school.